Entre a necessidade e a responsabilidade: desafios das redes de apoio de adultos e pessoas idosas dependentes de cuidados - Machado, Flávia Martins (2025)
This study focuses on health and people dependent on care, specifically the transition to dependency in the context of healthcare and its implications for care and social protection. Its general objective is to identify the challenges faced in caring for adult and elderly patients who have become dependent, considering the impacts on their support networks. This is an exploratory study with a qualitative approach and bibliographic methodological procedures. Sources were selected from scientific databases such as the CAPES Thesis and Dissertation Catalog and Google Scholar, delimiting the period from 2020 to 2025. The results indicate that the transition to dependency involves clinical, emotional, and social transformations, impacting family dynamics. Caregiving remains strongly associated with the domestic environment and women, revealing inequalities of gender, class, and race. Among the main challenges are the physical and emotional burden on caregivers, the fragility of support networks, and insufficient institutional responses. In this context, strategies such as caregiver training, strengthening home care, and intersectoral integration have proven fundamental to ensuring continuity, quality, and equity in care. Thus, the study reaffirms caregiving as a right and a collective responsibility.